Pengaruh Metode JASPER Untuk Meningkatkan Komunikasi Sosial Pada Anak Autism Spectrum Disorder Di Kawasan Teluk Gong Jakarta Utara - Chintia Indriati; Sudarman .; Nadya Susanti (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study aims to test the effect of the JASPER method to improve social communication in children with Autism Spectrum Disorder in the Teluk Gong area of ​​North Jakarta. This study uses a quantitative experimental approach with a one-group pretest-posttest design involving 10 children with Autism Spectrum Disorder aged 2 to 12 years as samples. The instruments used are the JASPER method module as a guide when conducting treatment and a Social Communication Skills questionnaire with adequate validity and reliability tests. Data analysis used is univariate analysis to see the frequency of distribution and percentage of each variable and the Wilcoxon bivariate test using SPSS 27, 2020. The results of the study indicate the effect of the JASPER method to improve social communication in children with Autism Spectrum Disorder in the Teluk Gong area of ​​North Jakarta (r = 0.005, p <0.05) meaning there is an effect between before and after being given the JASPER method intervention/treatment. These findings indicate that the JASPER method is a proven method to help children with Autism Spectrum Disorder to improve their social communication skills. This research hopes to be a reference for speech therapists, educators, parents, future researchers and professional organizations.